Deep brain stimulation for the treatment of substance use disorders: a promising approach requiring caution - Sakai, Joseph T.; Tanabe, Jody; Battula, Sharonya; Zipperly, Morgan; Mikulich-Gilbertson, Susan K.; Kern, Drew S.; Thompson, John A.; Ojemann, Steven; Raymond, Kristen; Gerecht, Pamela David; Foster, Katrina; Abosch, Aviva (Frontiers in Psychiatry, 2024)
Substance use disorders are prevalent, causing extensive morbidity and mortality worldwide. Evidence-based treatments are of low to moderate effect size. Growth in the neurobiological understanding of addiction (e.g., craving) along with technological advancements in neuromodulation have enabled an evaluation of neurosurgical treatments for substance use disorders. Deep brain stimulation (DBS) involves surgical implantation of leads into brain targets and subcutaneous tunneling to connect the leads to a programmable implanted pulse generator (IPG) under the skin of the chest. DBS allows direct testing of neurobiologically-guided hypotheses regarding the etiology of substance use disorders in service of developing more effective treatments. Early studies, although with multiple limitations, have been promising. Still the authors express caution regarding implementation of DBS studies in this population and emphasize the importance of safeguards to ensure patient safety and meaningful study results. In this Perspectives article, we review lessons learned through the years of planning an ongoing trial of DBS for methamphetamine use disorder.